The Properties of Exosomes Derived from Mesenchymal Stem Cells Preconditioned with L-Ascorbic Acid and Cobalt (II) Chloride - Anggraini Barlian; Rizka Musdalifah Amsar; Salindri Prawitasari; Christofora Hanny Wijaya; Ika Dewi Ana; Triati Dewi Kencana Wungu (Bogor Agricultural University, Indonesia, 2023)
Extracellular vesicles including exosomes, are produced by cells for intracellular communication. Preconditioning of parental cells influences exosome properties. The purpose of this study was to examine the effects of L-ascorbic acid (LAA) and cobalt (II) chloride (CoCl2) on human Wharton’s jelly mesenchymal stem cell (hWJ-MSC)-derived exosomes and their ability to promote stem cell differentiation into chondrocytes. The cells were isolated from the umbilical cord and characterized according to the criteria for mesenchymal stem cell. The cells were cultured in a serum-free medium containing LAA and CoCl2. Cell-produced exosomes were isolated and characterized. hWJ-MSCs can grow in serum-free medium containing LAA and CoCl2. Exosomes derived from hWJ-MSCs had a round morphology, particle size within the exosome range, CD 63 expression, and the capacity to be internalized by cells. The production of exosomes by hWJ-MSCs was enhanced by LAA treatment. LAA and CoCl2 promoted stem cell differentiation into chondrocytes, as indicated by the production of collagen type II and glycosaminoglycans. LAA and CoCl2 affect the properties of MSC-derived exosomes. LAA induces cells to produce exosomes in greater quantities, which have the potential to promote chondrogenic differentiation of stem cells.